ESTABLISHMENT AND DEVELOPMENT OF THE SOVIET SYSTEM OF GENERAL EDUCATION IN THE NORTH CAUCASUS (1920-1940) (Basing on the material from the autonomous republics of the region) - Kajmarazov, G S (History, Archeology and Ethnography of the Caucasus, 2015)
Despite the great number of publications on the history of education in various national autonomies of the North Caucasus, in the regional historiography there are no studies dealing with the problem of formation and development of the system of general education in the region in whole. Meanwhile, a comprehensive coverage of this extremely important part of the cultural sphere during the first decades of the Soviet power is of great educational, scientific and practical interest, taking into account peculiarities of cultural and historical process in this multicultural and multilanguage region. Basing on the rich source material, allowing for the achievements of domestic and world historiography, the author recreates a reliable picture of the formation and development of the system ofgeneral education in the 20-30s in the Dagestan, Kabardino-Balkarian, North Ossetian and Chechen-Ingush Autonomous Soviet Socialist Republics.
Keywords: Russian Federation; North Caucasus region; Dagestan; Kabardino-Balkaria; North Ossetia; Checheno-Ingushetia; culture; school; education; general education; teacher; writing; literacy; educational literature; teacher training college; college of education; teacher’s institute.